Športna dejavnost, učni uspeh in samopodoba štirinajstletnih učencev in učenk - Meško, Maja (Šport (Ljubljana), 2013)
The purpose of this study was to determine whether there are differences in learning achievements and self-esteem of fourteen-year old pupils according to how often they engaged in sports. We tried to find out whether pupils, who are more often involved in sport activities, have better self-esteem and better learning achievement, and whether pupils with better learning achievement have better self-esteem. We interviewed 168 9th grade primary school pupils. The data was analyzed with the statistical program SPSS. To determine differences between variables, we used analysis of variance. The results showed that more active pupils in terms of sport activities have better learning performance, and better self-esteem. Pupils who are more involved in sport much more, then pupils who are less involved in sport, believe that they have classmates who like them, they feel good in their skin, they think the pupils of opposite sex like them, and they believe that they can achieve success in their profession life. We also found out that pupils with better learning achievement have better self-esteem, they also think classmates like them, and believe that they can achieve a lot in their profession life. According to our results we assume that dealing with the relevant sports activities helps to improve the learning achievement and the development of positive self-esteem in adolescents. That is why pupils and adolescents need to be constantly encouraged for sport activities and we need to enable them to have regular sport activities, as thus enhancing self-image and self-esteem and has a positive influence on their learning achievement.
Keywords: learning achievement; osnovna šola; osnovne šole; primary school; pupil; samopodoba; school performance; self-concept; sport; sport activity; šport; športna dejavnost; učenci; učenec; učni uspeh; vprašalnik